Investigating the factors influencing the resilience of medium-sized commercial fishing enterprises in the Eastern Cape province - Mfono, Vuyisa Nomkhitha (Rhodes University, Faculty of Commerce, Rhodes Business School)
This research took the form of a case study of a media company, Kagiso Media (KM), that had been through a process of change. The company adopted a branding approach and used internal branding activities to implement a change intervention, which was unconventional and a unique approach, making it worthy of investigation. The primary aim of the study was, therefore, to analyse how a change in brand ideology (i.e. encompassing the business mission, vision, goals and shared values) shaped the senior leadership behaviour at KM and also led to the development of an improved performance management system. A case study research method was used. Data was collected through face-to-face and online interviews with the leadership team and combined with relevant company documents. A deductive thematic approach was used to analyse the data. The study revealed that brand ideology can impact leadership behaviour and performance if implemented deliberately. When the new CEO was appointed, his starting point was to change the KM brand ideology. The study revealed that, because of greater clarity in brand ideology, leadership behaviour improved. There were shifts in the manner in which leadership behaved and how they handled performance as a result of entrenching the new brand ideology. The study also revealed that the development of brand ideology necessitated changes in the performance management system. Brand-centred performance management systems contributed towards building a performance culture. In essence, developing a clear brand ideology was central to changing leadership behaviour and the revision of the performance management performance system. While limitations of the study are acknowledged, it has contributed by offering a unique perspective of an internal branding driven change and demonstrates how a change in brand ideology can impact leadership behaviour and performance management. Furthermore, the study recommended that further research could be done to include the perspectives of staff beyond the leadership team.
Keywords: Small business -- South Africa -- Eastern Cape; Fisheries Economic aspects -- South Africa -- Eastern Cape; Small and medium enterprises; Organizational resilience; Commercial fishing